Sharkbait - Baker, Howard E.; Clevenger, Scott.; Dippé, Mark A. Z.; Fox, John.; Lee, Young Ki.; Prinze, Freddie, Jr.; Schneider, Rob.; Shah, Ash R.; Wood, Evan Rachel, 1987- (CJ Entertainment, 2006)
Un joven pescado debe proteger su hogar y su verdadero amor de un tiburón intimidador.